Legal Problems of Collusion Among Law Enforcement Officials in Protecting the Distribution of Narcotics in Government Environments - Sunardi Sunardi; KMS Herman (Greenation International Journal of Law and Social Sciences, 2025)
The collusion of law enforcement officers in protecting the circulation of narcotics within the government is a serious phenomenon that threatens the integrity of the legal system and state security. This study aims to analyze this problem from a criminological and legal perspective. A criminological approach employs to identify the causal factors, modus operandi patterns, and impacts of crimes committed by officers, with reference to the theories of White-Collar Crime, State Crime, and Organized Crime. The results of the analysis indicate that economic factors such as bribery and gratuities, weak structural oversight, and low moral integrity of officers are the main drivers of the conspiracy. The modes found include manipulation of evidence, protection of certain networks, and abuse of authority to facilitate the distribution of narcotics, including in correctional institutions. The legal approach explains the relevant legal framework, including Articles 112, 114, and 132 of Law Number 35 of 2009 concerning Narcotics; Articles 5, 6, 11, and 12 of Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption; and Articles 421, 422, 55, and 56 of the Criminal Code. The analysis reveals weak provisions for imposing increased sanctions on involved officers and ineffective external oversight mechanisms. The study's conclusions confirm a close relationship between regulatory weaknesses and the prevalence of collusion among officers, necessitating revisions to the Narcotics Law, strengthening independent oversight, protecting witnesses and whistleblowers, and fostering officer integrity. Implementing these recommendations is expected to break the chain of officer involvement in drug trafficking networks and restore public trust in law enforcement.